ASSESSING THE IMPACTS OF CLIMATIC FACTORS ON COTTON YIELD AND ITS ECONOMIC INDICATORS - Assem A. A. MOHAMED; Mona MAZE; Mohamed M. M. ABDELAZIZ; Alaa A. KHALIL (Journal of Applied Life Sciences and Environment)
Cotton is one of the strategic crops in Egypt. This article investigates the impacts of climatic factors and their variations on the cotton yield and its economic benefits during the period from 1998 to 2019. We chose the Kafr El-Sheikh Governorate, where cotton is one of the major planted crops, was chosen for the analysis. The climatic factors utilized were the maximum, minimum and average temperatures; relative humidity; solar radiation and wind speed. Precipitation was excluded, as Egypt depends mainly on irrigation. The climatic factors utilized influenced yield during different growth stages: wind speed showed an influence only on the germination stage, whereas temperature had a major impact before and at the maturity stages. The latter correlation was positive in July and negative in August and September. Relative humidity and solar radiation impacted on yield at different growth stages, with an almost positive correlation with solar radiation and both a positive and a negative correlation with relative humidity. For the study of the economic indicators of cotton, cotton data were taken for the whole Egyptian Governorate during the period 2005-2019. The study showed a decrease in the net return during the period from 2005 to 2015 that reached a loss (minus value) of 195 Egyptian pounds (LE) in 2015, followed by an increase during the period from 2016 to 2019 due to the increase in farm gate prices.